A theory of craft : function and aesthetic expression - Risatti, Howard, 1943- (University of North Carolina Press, 2007)
What is craft? How is it different from fine art or design? Risatti examines these issues by comparing handmade ceramics, glass, metalwork, weaving, and furniture to painting, sculpture, photography, and machine-made design from Bauhaus to the Memphis Group. He describes craft's unique qualities as functionality combined with an ability to express human values that transcend temporal, spatial, and social boundaries. Craft must articulate a role for itself in contemporary society, says Risatti; otherwise it will be absorbed by fine art or design and its singular approach to understanding the world will be lost.- Resumé vydavatel
Keywords: řemesla; dekorativní umění; design; filozofie; handicrafts; decorative arts; philosophy; elektronické knihy; monografie; electronic books; monographs